The Impact of Oxidative Stress on Obesity Development : Biochemical Evidence and Potential Therapeutic Approaches - Dyah Wulandari Putri, Putu; Made Wihandani, Desak; Made Winarsa Ruma , I (Syntax Corporation, 2026)
Obesity is a global public health concern with rising prevalence, affecting approximately one in eight adults worldwide. Oxidative stress has been identified as a key factor in the pathogenesis of obesity and its complications. Objective: This review aims to explore the biochemical mechanisms linking oxidative stress to obesity development and to examine potential therapeutic strategies targeting oxidative stress pathways. Method: This study is a narrative review employing a comprehensive literature search of PubMed and Google Scholar using keywords related to obesity, oxidative stress, ROS, inflammation, adipogenesis, insulin resistance, and therapeutic approaches. Selected articles were English-language publications from the last decade and available in full-text format. Results: Oxidative stress plays a central role in obesity through multiple biochemical mechanisms. ROS activate inflammatory pathways by inducing M1 macrophage polarization and increasing pro-inflammatory cytokine expression via NF-κB activation. In adipogenesis, physiological ROS levels facilitate preadipocyte differentiation through PPARγ regulation, while excessive ROS cause adipocyte dysfunction and alterations in the pro-inflammatory adipokine profile. ROS also disrupt insulin signaling through JNK activation, which phosphorylates IRS-1 at serine residues. Therapeutic strategies targeting oxidative stress include dietary modifications (such as the Mediterranean diet), antioxidant supplementation, regular physical activity, pharmacological agents (rapamycin, orlistat, resveratrol), microbiota modulation, and advanced approaches including nano-formulations and gene therapy. Implications: A deep understanding of the molecular mechanisms of oxidative stress in obesity may lead to the development of more effective and personalized therapeutic strategies for managing obesity and related metabolic complications.